Revealing Possible Truths Behind “Coolest Monkey in The Jungle”: Ideational Making Analysis Approach - Imam Khasbani (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2018)
Multimodal Critical Discourse Analysis (CDA)-commonly defined as a discourse analysis approach that focuses on both linguistic and non-linguistic resources- has been witnessing increasing popularity in the research area. It has been argued, on the one hand, that the greater level of practicality the approach has to offer compared to its predecessor (Critical Discourse Analysis) becomes the main reason of why researchers gradually turn their reference on analysing discourses to this method (Han, 2015). An increasing trend of multimodal communications - that no longer use speech or writing exclusively in their occurrences - has become the logical ground on the other (Kress, 2011). This paper, using H&M ‘monkey’ hoodie advertisement (refer to appendix) as a form of multimodal communication, employs MCDA to explore the possible advantages one can learn through the process. To start with, a brief account of the key factors in the development of MCDA will be presented. This part is then followed by the discussion of the analysis approach employed in the paper and also the rational basis for choosing the approach over others. The analysis of the advertisement is done by drawing on related language and social theories to scrutinize the ideologies the company implanted on their advertisement. A thoughtful discussion on what is understood through the analysis process and what and how one can relate the practicality of multimodality analysis to another social area such as pedagogy will mark the end of this paper’s discussion.